Endovascular versus surgical creation of arteriovenous fistula in hemodialysis patients: Cost-effectiveness and budget impact analyses. Issue 1 (January 2021) - Rognoni, Carla; Tozzi, Matteo; Tarricone, Rosanna
Objectives: The aim of the present study was to perform cost-effectiveness and budget impact analyses comparing endovascular arteriovenous fistula creation to surgical arteriovenous fistula creation in hemodialysis patients from the National Healthcare Service (NHS) perspective in Italy. Methods: A systematic literature review has been conducted to retrieve complications' rates after arteriovenous fistula creation procedures. One study comparing endovascular arteriovenous fistula creation, performed with WavelinQ device, to the surgical approach through propensity score matching was preferred to single-arm investigations to execute the economic evaluations. This study was chosen to populate a Markov model to project, on a time horizon of 1 year, quality adjusted life years and costs associated with endovascular arteriovenous fistula (WavelinQ) and surgical arteriovenous fistula options for both cohorts of incident and prevalent hemodialysis patients. Results: For both incident and prevalent hemodialysis patients, endovascular arteriovenous fistula creation, performed with WavelinQ, was the dominant strategy over surgical arteriovenous fistula approach, showing less cost and better patients' quality of life. Compared to the current scenario, progressively increasing utilization rates of WavelinQ over surgical arteriovenous fistula creation in the next 5 years in incident hemodialysis patients are expected to save globally 30–36 million euros to the NHS. Conclusion: Endovascular arteriovenous fistula creation performed with WavelinQ could be a cost-saving strategy in comparison with the surgical approach for patients in hemodialysis. Future studies comparing different devices for endovascular arteriovenous fistula creation versus the surgical option would be needed to confirm or reject the validity of this preliminary evaluation. In the meantime, decision-makers can use these results to take decisions on the diffusion of endovascular procedures in Italy.